Impact of Sample Collection Order on the Diagnostic Performance of Metagenomic Deep Sequencing for Infectious Keratitis. Issue 1 (15th January 2022) - Redd, Travis K.; Lalitha, Prajna; Prajna, N. Venkatesh; Sikha, Misra; Gunasekaran, Rameshkumar; Hinterwirth, Armin; Chen, Cindi; Zhong, Lina; Liu, Zijun; Lietman, Thomas M.; Keenan, Jeremy D.; Doan, Thuy; et al.
Abstract : Purpose: The purpose of this article was to evaluate the impact of sample collection order on the diagnostic yield of metagenomic deep sequencing (MDS) for determining the causative pathogen in infectious keratitis. Methods: We performed a cross-sectional diagnostic test evaluation among subjects with infectious keratitis at Aravind Eye Hospital in Madurai, India. All subjects underwent corneal scrapings of the affected eye to obtain potassium hydroxide smear, Gram stain, bacterial culture, and fungal culture, in this order. The order of MDS specimen collection relative to smear and culture samples was randomized and served as the primary predictor. Outcomes included the normalized copy number of pathogenic RNA detected by MDS, the proportion of MDS samples that were diagnostic, and the agreement of MDS results with cultures. Results: MDS samples from 46 subjects with corneal ulcers were evaluated. MDS was positive in 33 subjects (76%) and had 74% overall agreement with culture results. There was no association between order of MDS sample collection and normalized copy number of genetic material detected ( P = 0.62) or the likelihood of MDS positivity ( P = 0.46). However, the likelihood of agreement between MDS and cultures decreased when MDS corneal swabs were collected after other diagnostic corneal scrapings ( P = 0.05). Conclusions: The overall yield of MDS for detecting the cause of infectious keratitis was not affected by sample collection order. However, diagnostic agreement between MDS and cultures decreased when MDS samples were collected after other specimens. Additional investigation is warranted to determine whether this represents increased sensitivity of MDS compared with cultures or higher susceptibility to contaminants.